Double Salts Iodide Scintillators: Cesium Barium Iodide, Cesium Calcium Iodide, and Barium Bromine Iodide. Issue 4 (13th March 2013) - Rowe, E.; Tupitsyn, E.; Wiggins, B.; Bhattacharya, P.; Matei, L.; Groza, M.; Buliga, V.; Burger, A.; Beck, P.; Cherepy, N.J.; Payne, S.A.
Abstract In this study we review the state‐of‐the‐art for double salt iodide scintillators, in particular cesium barium iodide (CBI), cesium calcium iodide (CCI) and barium bromine iodide (BBI), as well as report on their scintillation and optical properties. Double salt iodides inherently have high density and atomic number which translates to good stopping power for energetic particles, in particular gamma rays. Light yields of 54, 000 ph/MeV for CBI, 51, 000 ph/MeV for CCI, and 46, 000 ph/MeV for BBI were measured. A FWHM energy resolution for the 662 keV full absorption peak was observed at 5.7% for CBI, 16.3% for CCI and 3.56% for BBI. The principal scintillation decay timing for CBI was 840 ns, 462 ns for BBI, and two distinct time components of 9 ns and 1900 ns were observed for CCI.